2011
DOI: 10.1016/j.bpj.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Single Particles and Elongated Filaments with Nanometer Precision

Abstract: Recent developments in image processing have greatly advanced our understanding of biomolecular processes in vitro and in vivo. In particular, using Gaussian models to fit the intensity profiles of nanometer-sized objects have enabled their two-dimensional localization with a precision in the one-nanometer range. Here, we present an algorithm to precisely localize curved filaments whose structures are characterized by subresolution diameters and micrometer lengths. Using surface-immobilized microtubules, fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
287
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(287 citation statements)
references
References 37 publications
0
287
0
Order By: Relevance
“…1 B for the definition of these motility parameters), we used the open-source tracking software FIESTA (20). We found that all three quantities decreased significantly upon increasing the roadblock concentration (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…1 B for the definition of these motility parameters), we used the open-source tracking software FIESTA (20). We found that all three quantities decreased significantly upon increasing the roadblock concentration (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…S6). Two-dimensional trajectories of AuNP-loaded motors were then projected onto the MT centerline using FIESTA (20). Single-molecule conditions, i.e., conditions under which AuNP transportation was driven by individual motors, were ensured by optimizing the incubation ratios of AuNPs to motors such that the motility parameters of loaded and unloaded motors in the absence and presence of roadblocks were the same (Supporting Material D, Fig.…”
Section: Motors Circumvent Roadblocks By Unbiased Sideshifting To Thementioning
confidence: 99%
See 1 more Smart Citation
“…Many particle tracking methods solve the correspondence problem in a spatially global manner (Chetverikov and Verestói, 1999;Genovesio et al, 2006;Ruhnow et al, 2011;Sbalzarini and Koumoutsakos, 2005;Thomann et al, 2002;Tvaruskó et al, 1999;Veenman et al, 2003). For example, some level of global optimization can be achieved using graph theory, as in the publicly available software ParticleTracker (Sbalzarini and Koumoutsakos, 2005).…”
Section: Background Informationmentioning
confidence: 99%
“…Q-dots were tracked from sequential TIFF images using FIESTA software 52 . The obtained trajectories were further analysed with MatLab 2013b (MathWorks).…”
Section: Imaging and Data Processingmentioning
confidence: 99%